Trapped free: school responses to institutional logics in quasi-markets - Dahle, Dag Yngve (Frontiers in Education, 2025)
IntroductionThis paper examines how brand-sensitive public sector schools respond to marketization and branding pressure, and whether and how responses differ between marginalised and privileged schools.MethodsTextual statements on the social media profiles of upper secondary schools in Oslo and two surrounding areas were examined by content analysis with thematic coding. Marginalised and privileged schools were identified by admission statistics for public sector upper secondary schools.ResultsThe study uncovers that market position influences branding strategies, with privileged schools adopting more differentiating branding than marginalized ones. The study identifies six ideal types of schools which represent a typology of different response strategies related to market-driven branding pressures.DiscussionConsequently, it is difficult for schools to avoid or defy branding pressure and not engage in branding efforts, which, in turn, adds to marketization, making it even more difficult to break free from the negative spiral.